(untitled) (Research, Society and Development, 2020)
Yerba mate (Ilex paraguariensis A. St.-Hil.) is an importance species of the Southern Brazilian silviculture. Besides the traditional ‘terere’ and ’chimarrão’ beverage, also called ’mate’, its raw material is used in the production of food, beverages, cosmetics, hygiene products and important medicines. Its raw material has been applied in the production of food, beverages, cosmetics, cleaning products and important medicines. Recently there has been an increase in demand for products derived from yerba mate in several countries, such as Italy, Spain and the United States. However, yerba mate crop still suffers some problems, mainly regarding the production of yerba mate seedlings. These, in most cases, are obtained via sexual propagation, which may result in low yield and final product quality, which may lead to decreased profitability for field producers. All of this due to the lack of efficient protocols for clonal propagation of yerba mate, as well as, the knowledge about the factors that interfere in the rooting process, hormonal balance, use of rooting inducers, collection time of propagules, progenitor age, rooting environment, substrates and nutrient solutions. As for the method used to carry out the research, a bibliographic review was used as a tool to investigate the factors influencing the rooting of cuttings and mini-cuttings in yerba mate, addressing scientific data published from 2009 with vegetative propagation by cuttings and mini-cuttings of Ilex paraguariensis. The purpose of this review is to verify the state of the art and the viability of vegetative propagation by cuttings and mini-cuttings of yerba mate.